The Effect of Promotion through Instagram Social Media on Purchasing Decisions at Chocolicious Cake Stores in Makassar City - Mochtar Luthfi M; Nur Afni Pertiwi (Journal La Bisecoman, 2020)
This study aims to determine and analyze the effect of promotion through social media Instagram on purchasing decisions at a chocolicious cake shop in Makassar City. Customer Study of Chocolicious Cake Shop on Jln A.P. Pettarani Makassar. The research method used in this research is descriptive quantitative, with a total sample of 60 respondents. The analytical method used in this study is a simple regression analysis using SPSS 24. The results showed that promotion through social media Instagram had a positive and significant effect on purchasing decisions with the results of the t count> t table (6.564> 1.671). Chocolicious products are accepted by the public and also show that indeed social media has an important role in conveying information such as introducing products to the general public if we are good at using them.